The Role of Human Resource Management (Teachers) in Improving Learning Creativity in Schools - Hasanah Hasanah; Syifa Ayu Fauziyyah (Indonesian Journal of Innovative Teaching and Learning, 2025)
Background: In an era of rapid educational transformation, schools are increasingly challenged to foster student creativity through innovative teaching practices. One key factor influencing this is the effective management of human resources, particularly teachers, who serve as the primary agents in the learning process. Objective: This study examines the role of human resource management (teachers) in enhancing learning creativity at SMPIT Assyifa Boarding School Subang. Method: A field research approach was used, with data collected through observations, documentation, and triangulation for validity. Data analysis involved three stages: data reduction, presentation, and conclusion drawing. Results: The study found that improving teacher creativity involves various strategies, including workshops, training, comparative studies with other schools, enhancing learning facilities and infrastructure, curriculum development, and fostering collaboration among educational stakeholders. Conclusion: Effective human resource management strategies can enhance teacher creativity, ultimately improving the learning process. Contribution: This study provides practical insights into optimizing teacher development programs to foster creativity in education.